2018
DOI: 10.1523/jneurosci.1291-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 Is Essential for Oligodendroglial Proliferation and Differentiation during Postnatal Brain Myelination and CNS Remyelination

Abstract: In the CNS, myelination and remyelination depend on the successful progression and maturation of oligodendroglial lineage cells, including proliferation and differentiation of oligodendroglial progenitor cells (OPCs). Previous studies have reported that Sox2 transiently regulates oligodendrocyte (OL) differentiation in the embryonic and perinatal spinal cord and appears dispensable for myelination in the postnatal spinal cord. However, the role of Sox2 in OL development in the brain has yet to be defined. We n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 42 publications
10
101
0
Order By: Relevance
“…In MOLs, SOX2 expression is markedly downregulated, as are many of the genes within its regulatory network. Given that SOX2 expression is necessary for proper remyelination in the adult brain (Zhang et al, ), the network of genes proximally regulated by SOX2 would be informative to study in the context of remyelination failure.…”
Section: Discussionmentioning
confidence: 99%
“…In MOLs, SOX2 expression is markedly downregulated, as are many of the genes within its regulatory network. Given that SOX2 expression is necessary for proper remyelination in the adult brain (Zhang et al, ), the network of genes proximally regulated by SOX2 would be informative to study in the context of remyelination failure.…”
Section: Discussionmentioning
confidence: 99%
“…To define the role of physiological HIFα stabilization in developmental myelination, we used Cre-loxP-based genetic approach to conditionally disrupt HIFα function. Previous studies have demonstrated that Pdgfrα-CreER T2 drives gene disruption in OPCs whereas Cnp-Cre in later stages of oligodendrocyte development (Moyon et al, 2016;Zhang et al, 2018a;Zhang et al, 2018b). Our extensive analysis of HIF1α or HIF2α conditionally knockout mice driven by Pdgfrα-CreER T2 and Cnp-Cre revealed no phenotypic abnormalities of the oligodendroglial lineage, suggesting functional redundancy between HIF1α and HIF2α.…”
Section: Disrupting Hifα In Opcs But Not Ols Delays Developmental Myementioning
confidence: 51%
“…Tamoxifen was administered to PDGFRα:HIFα cKO and non-Cre littermate control (Hif1α fl/fl :Hif2α fl/fl ) pups at P1, P2, and P3 and the CNS tissue was analyzed at P8. Our previous data show that this tamoxifen paradigm induces ~90% of gene cKO efficiency in OPCs (Zhang et al, 2018a;Zhang et al, 2018b). The density of differentiated OLs but not OPCs was significantly decreased in the spinal cord white matter of PDGFRα:HIFα cKO mice compared with non-Cre littermate controls ( Fig.…”
Section: Disrupting Hifα In Opcs But Not Ols Delays Developmental Myementioning
confidence: 69%
See 1 more Smart Citation
“…In addition, vitamin D3-induced transcription factors (GO Cellular Component (GO-CC) "nuclear transcription factor complex", Supplementary Fig. S2) included Sox2, whose role in OL differentiation was recently reported 45,46 and CCAAT/enhancer binding protein beta (Cebpb), a VDR-responsive gene that controls the differentiation of myeloid leukaemia cells 47 .…”
Section: Functional Enrichment Analysis Of the Genes Uniquely Down-rementioning
confidence: 99%